2023
DOI: 10.1002/eat.23892
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders and substance use: Examining associations among US college students

Abstract: Objective To investigate associations between reported eating disorder (ED) diagnosis and substance use disorder (SUD) diagnosis, substance misuse, and illicit drug use among US college students. Method Data consisting of n = 414,299 students' responses to the National College Health Assessment survey conducted by the American College Health Association between fall 2015 and spring 2019 were utilized for this study. Unadjusted and adjusted odds ratios were used to determine the association of reported ED diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
3
5
0
Order By: Relevance
“…Our study is unique in that it expands on previous ACHA‐NCHA studies by addressing identity intersectionality, looking at more than one identity at a time. Our findings expand upon the work of previous researchers who also utilized the ACHA‐NCHA data to explore various aspects of eating disorders among college students (Claydon & Zullig, 2020; Duffy et al, 2019; Matthews‐Ewald et al, 2014; Qeadan et al, 2023; Schiros & Antshel, 2023; Van Dyne et al, 2023). Our findings were consistent with Matthews‐Ewald et al (2014) who observed higher odds of EDs and disordered eating behaviors among sexual minorities (i.e., gay, unsure, and bisexual men compared to heterosexual men).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our study is unique in that it expands on previous ACHA‐NCHA studies by addressing identity intersectionality, looking at more than one identity at a time. Our findings expand upon the work of previous researchers who also utilized the ACHA‐NCHA data to explore various aspects of eating disorders among college students (Claydon & Zullig, 2020; Duffy et al, 2019; Matthews‐Ewald et al, 2014; Qeadan et al, 2023; Schiros & Antshel, 2023; Van Dyne et al, 2023). Our findings were consistent with Matthews‐Ewald et al (2014) who observed higher odds of EDs and disordered eating behaviors among sexual minorities (i.e., gay, unsure, and bisexual men compared to heterosexual men).…”
Section: Discussionsupporting
confidence: 80%
“…Our study is unique in that it expands on previous ACHA-NCHA studies by addressing identity intersectionality, looking at more than one identity at a time. Our findings expand upon the work of previous researchers who also utilized the ACHA-NCHA data to explore various aspects of eating disorders among college students (Claydon & Zullig, 2020;Duffy et al, 2019;Matthews-Ewald et al, 2014;Qeadan et al, 2023;Schiros & Antshel, 2023;Van Dyne et al, 2023) (Duffy et al, 2019). Second, students with anorexia nervosa and bulimia nervosa who were treated with medication and psychotherapy reported improved academic performance and grade point averages (Claydon & Zullig, 2020).…”
Section: Identity Intersectionalitysupporting
confidence: 77%
See 2 more Smart Citations
“…Emerging adulthood (ages 18 to 25) is a period of several life transitions characterized by increased risk and impulsivity related to addictive health behaviors and is a particularly high-risk period for binge drinking and binge eating in women ( Arnett, 2005 , Grucza et al, 2018 , Qeadan et al, 2023 , Sonneville et al, 2013 , Sussman and Arnett, 2014 ). The term “binge” refers to a pattern of excessive consumptive behavior that occurs in a short, discrete period of time ( Escriva-Martinez et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%